Approaches and methods to educational policy analysis: first approaches - Laélia Portela Moreira (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2017)
The field of educational policy, despite its relative youth and its origins in political science, already has some specific proposals for relevant research, such as the Policy Cycle Approach, the Approach of Educational Policy Epistemologies (EEPE), Social Cartography and Critical Discourse Analysis, among others. These models aim to contribute to the consolidation of research in this field, within the limits allowed by its meta-analytical character, considering also the presuppositions and theoretical affiliations assumed by its researchers. This descriptive-analytical pluralistic and introductory text aims to present some of the appropriate approaches for research in the field of educational policy from the recognition of its relevance to the training of new researchers. The text is divided into two main parts. The first presents a brief characterization of the field and discusses some issues related to the research concerned. Next, four general approaches are presented for the field research, with the intention of mapping them to those interested in furthering them.